Pharmacological postconditioning with atorvastatin calcium attenuates myocardial ischemia/reperfusion injury in diabetic rats by phosphorylating GSK3β - Chen, Linyan (Exp Ther Med, 2017)
Diabetes is an independent risk factor for myocardial ischemia, and many epidemiological data and laboratory studies have revealed that diabetes significantly exacerbated myocardial ischemia/reperfusion injury and ameliorated protective effects. The present study aimed to determine whether pharmacological postconditioning with atorvastatin calcium lessened diabetic myocardial ischemia/reperfusion injury, and investigated the role of glycogen synthase kinase (GSK3β) in this. A total of 72 streptozotocin-induced diabetic rats were randomly divided into six groups, and 24 age-matched male non-diabetic Sprague-Dawley rats were randomly divided into two groups. Rats all received 40 min myocardial ischemia followed by 180 min reperfusion, except sham-operated groups. Compared with the non-diabetic ischemia/reperfusion model group, the diabetic ischemia/reperfusion group had a comparable myocardial infarct size, but a higher level of serum cardiac troponin I (cTnI) and morphological alterations to their myocardial cells. Compared with the diabetic ischemia/reperfusion group, the group that received pharmacological postconditioning with atorvastatin calcium had smaller myocardial infarct sizes, lower levels of cTnI, reduced morphological alterations to myocardial cells, higher levels of p-GSK3β, heat shock factor (HSF)-1 and heat shock protein (HSP)70. The cardioprotective effect conferred by atorvastatin calcium did not attenuate myocardial ischemia/reperfusion injury following application of TDZD-8, which phosphorylates and inactivates GSK3β. Pharmacological postconditioning with atorvastatin calcium may attenuate diabetic heart ischemia/reperfusion injury in the current context. The phosphorylation of GSK3β serves a critical role during the cardioprotection in diabetic rats, and p-GSK3β may accelerate HSP70 production partially by activating HSF-1 during myocardial ischemic/reperfusion injury.